An Innovative Model of Bronchopulmonary Dysplasia in Premature Infants - Zhang, Xiaoyue; Chu, Xiaoyun; Weng, Bowen; Gong, Xiaohui; Cai, Cheng (Frontiers in Pediatrics, 2020)
Bronchopulmonary dysplasia (BPD) is one of the common chronic lung diseases (CLD) of premature infants, which causes unpredictable consequences to the family and society. Therefore, the pathogenesis and prevention methods of BPD are the focus of current research, and the establishment of an effective and appropriate animal model of BPD in premature infants is the key to the research. In this study, premature rats were exposed to hyperoxia environment. Compared with the air group, the body weight and alveolar radiation count of the hyperoxia group decreased significantly, but there was no significant difference in body length. HE staining was used to observe the pathological changes of BPD in the lung tissue. The above results proved that under the hyperoxia condition, the BPD animal model of premature infants was successfully established, which provided a new choice for the future research of BPD.